(untitled) (Agriculture, Food, and Natural Resources Journal, 2026)
Forest inventory is a crucial component of sustainable forest management that requires strong monitoring programmes. However, due to the perceived high cost of forest inventory, many forest managers do not regularly update growth characteristics information. Updated information on growth variables is essential for determining forest production potential and ensuring accountability for sustainable management. This study investigated inventory-based assessment of tree growth variables for mixed tropical species in Okomu Forest Reserve (OFR), Nigeria. Using a systematic sampling technique, 2,949 trees with diameter at breast height (DBH) ≥ 10 cm were assessed within 60 plots measuring 50 m × 50 m, alternately laid at 200 m intervals along 15 transects (1 km each). Tree growth variables measured included DBH and total height (TH). Other variables estimated were Basal Area (BA), Stem Volume (SV), Stand Density (N), Canopy Cover, and Slenderness Coefficient (SC). Data were analysed using descriptive statistics. Results showed that DBH and TH ranged from 10–197 cm, 6.0–48.0 m respectively. BA ranged from 9.0–42.8 m²/ha, SV (121.7–1094.0 m³/ha), and N (128–424 trees/ha). Canopy cover was approximately 48%. About 35% of the trees were within the diameter class ≤ 20 cm; 0.2% and 0.6% were within the 100–110 cm and >110 cm classes, respectively. TSC showed that 68 trees/ha had high SC (>80), 28 trees/ha were moderate (TSC: 70-80) and 101 trees/ha (<70) were low. The study concludes that growth variables provide essential baseline information for effective forest management and decision-making and recommends consistent updating of tree growth data